(untitled) - Murty, B. Padmanabha (New Delhi, 2004)
This is also a textbook and a reference book to Consultants in Environment as well as Scientists/engineers in States and Central pollution Control Boards and Industries like India Oil Corporation, National Thermal Power Corporation, etc. The book states that applications of meteorological principles to environmental problems, though broadly known, are neither widely understood nor studied in detail.
Keywords: Meteorology,Khí tượng học; Environmental aspects,Khía cạnh môi trường